Color stability of different composite resin materials bleached with three bleaching agents - Türker, Şebnem Begüm; Mandalı, Gamze; Buğurman, Burcu; Şener, Işıl Damla; Alkumru, Hasan Necdet (Marmara Dental Journal, 2013)
The aim of this study was to compare the color stability of 3 proprietary carbamide peroxide bleaching agents on composite resins. Specimens were prepared with a polytetrafluoroethylene plate. After initial color measurements, bleaching agents were applied to each composite resin for 2 weeks. Second color measurements were made. Tested specimens including control group were immersed into distilled water for a - 4 month follow-up period. Third and fourth color measurements were made again after 2 weeks and 4 months of follow-up period. Friedman (p<.01), Kruskal Wallis (p<.05) and Wilcoxon Tests were used for statistically evaluation. The most significant color change was seen at the Ormocer group (p<.011). The most significant color change ΔE values were obtained for the Ormocer-Voco group and color changes remained stable after 4 months of immersion in distilled water. Slight color changes values were obtained for nanohybrid and fine particle hybrid composite resins.
Keywords: Bleaching;restorative materials;color stability;